2014
DOI: 10.1007/s11837-014-0908-0
|View full text |Cite
|
Sign up to set email alerts
|

Design of Novel Bainitic Steels: Moving from UltraFine to Nanoscale Structures

Abstract: The concepts of phase transformation theory can be exploited to design nanostructured steels that transform to bainite at temperatures as low as 150 ºC. The microstructure obtained is so refined that it is possible to achieve a strength in excess of 2.5 GPa in a material which has considerable toughness (40 MPam 1/2). Such combination of properties has never been achieved before with bainite. A description of the characteristics and significance of this remarkable microstructure in the context of the mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 50 publications
3
37
0
1
Order By: Relevance
“…The retained austenite grains are extremely fine ($50 nm) and equiaxed. Recent studies have found inverse correlation between size of the austenite grain and amount of carbon dissolved in the solution [7]. The higher carbon in the retained austenite could occur from dissolution of carbides and movement of carbon out of martensite due to dislocation movement.…”
Section: Transmission Kikuchi Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retained austenite grains are extremely fine ($50 nm) and equiaxed. Recent studies have found inverse correlation between size of the austenite grain and amount of carbon dissolved in the solution [7]. The higher carbon in the retained austenite could occur from dissolution of carbides and movement of carbon out of martensite due to dislocation movement.…”
Section: Transmission Kikuchi Diffractionmentioning
confidence: 99%
“…The higher carbon in the retained austenite could occur from dissolution of carbides and movement of carbon out of martensite due to dislocation movement. It is also known that smaller grain size and higher amount of dissolved carbon significantly enhances mechanical stability of retained austenite [7]. In the application point of view, the retained austenite in the thermally transformed layer will have higher mechanical stability to resist the strain induced transformation (TRIP effect); on the other hand, it also means dramatic improvement in the dimensional stability.…”
Section: Transmission Kikuchi Diffractionmentioning
confidence: 99%
“…In general, low transformation temperatures are associated with fine microstructures which in turn generally possess both strength and toughness. Following this simple concept, a new generation of steels has been designed in which transformation at low temperature leads to a nanoscale microstructure consisting of extremely fine, 20-40-nmthick, plates of ferrite and retained austenite [7]. These microstructures are achieved through isothermal transformation to bainite of high carbon high silicon steels with low martensite start temperature (approx.…”
Section: Developing Nanocrystalline Steels By Displacive Reactionmentioning
confidence: 99%
“…At temperatures where the atomic mobility of carbon atoms is sufficient, there will then be a tendency for the austenite to decompose into a mixture of ferrite and cementite. Many studies have observed a carbon supersaturation with respect to cementite in both austenite [5,6,[10][11][12][13][14][15] and ferrite. [12,13,[15][16][17][18][19] There is therefore a large driving force for the formation of cementite in both phases.…”
Section: Introductionmentioning
confidence: 99%